Renewables-based technology : sustainability assessment - Dewulf, Jo, 1969-; Van Langenhove, Herman, 1953- (Chichester : Wiley, 2006)
Sustainability is a key driving force for industries in the chemical, food, packaging, agricultural and pharmaceutical sectors, and quantitative sustainability indicators are being incorporated into company reports. This is driving the uptake of renewable resources and the adoption of renewables. Renewables' can either be the substituted raw materials that are used in a given industry, (e.g. the use of biomass for fuel); the use and/or modification of a crop for use in a new industry (e.g. plant cellulose), or the reuse of a waste product (e.g. organic waste for energy production). This is the first book in the "Wiley Renewable Resources" series that brings together the range of sustainability assessment methods and their uses. Ensuing books in the series will look at individual renewable materials and applications.
Keywords: Duurzame energie